2008 Proceedings IEEE INFOCOM - The 27th Conference on Computer Communications 2008
DOI: 10.1109/infocom.2007.224
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and Modeling of the Origins of Starvation in Congestion Controlled Mesh Networks

Abstract: Abstract-Significant progress has been made in understanding the behavior of TCP and congestion-controlled traffic over multihop wireless networks. Despite these advances, however, no prior work identified severe throughput imbalances in the basic scenario of mesh networks, in which one-hop flows contend with two-hop flows for gateway access. In this paper, we demonstrate via real network measurements, test-bed experiments, and an analytical model that starvation exists in such a scenario, i.e., the one-hop fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 6 publications
0
25
0
1
Order By: Relevance
“…(Others have studied starvation in multi-hop networks [6,20].) Moreover, we assume the APs do not use RTS/CTS, since studies [9] show that RTS/CTS is unfair in a congested setting, and RTS/CTS is turned off by default in commercial devices.…”
Section: Problem Statementmentioning
confidence: 99%
See 1 more Smart Citation
“…(Others have studied starvation in multi-hop networks [6,20].) Moreover, we assume the APs do not use RTS/CTS, since studies [9] show that RTS/CTS is unfair in a congested setting, and RTS/CTS is turned off by default in commercial devices.…”
Section: Problem Statementmentioning
confidence: 99%
“…This paper is an attempt at improving the estimate in Eq. Shi et al [20] have studied the starvation problem of congestion-controlled traffic (TCP) in multi-hop wireless networks, where one-hop flows may contend with and starve two-hop flows. Our work differs from theirs in that we investigate the throughput of non-congestion-controlled traffic (UDP) in one-hop wireless networks, where the transmission range of different access points may overlap.…”
Section: Challengesmentioning
confidence: 99%
“…In our work, starting from a different view, we try to fulfil uplink throughput requirement and maximize the downlink throughput by tuning the window size instead of limiting the traffic rate. In [5], [13], the performance of multiple uni-directional TCP flows and their throughput fairness in a linear network is studied.…”
Section: Related Workmentioning
confidence: 99%
“…In particular, it has been demonstrated that nodes close to the gateway in the wireless backhaul 1 This work is in part supported by National Science Council under grant NSC 98-2221-E-194-030. network can starve those that are more hops away [1], [2], [3], [4], [5]. Eliminating the contention from hidden nodes is the key to providing high performance in the backhaul network.…”
Section: Introductionmentioning
confidence: 99%